1999
DOI: 10.1002/(sici)1098-2264(199909)26:1<80::aid-gcc11>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Loss of heteroplasmy in the displacement loop of brain mitochondrial DNA in astrocytic tumors

Abstract: The aim of this study was the determination of D‐loop heteroplasmy in astrocytic brain tumors. DNA fragments corresponding to the hypervariable region 2 of the mitochondrial displacement loop (D‐loop) from 12 astrocytic tumors and 2 corresponding brain samples were cloned into a plasmid vector. Heteroduplex analysis revealed high sequence variability in the brain samples and a subfraction of grade 2 and grade 3 tumors. Furthermore, the results were suggestive of a very low degree of heteroplasmy in all gliobla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 4 publications
1
21
1
Order By: Relevance
“…After controlling products on silver-stained polyacrylamide gels, samples were digested with HaeIII, creating a blunt end at np 333 immediately behind the polycytosine tract of interest. Using cloned and sequenced HVR2 fragments from an earlier study 21 and known HVR2 blood sequences, we could clearly determine the absolute length of the polycytosine tracts on a 373A sequencer (Applied Biosystems, Foster City, CA) by comparison with known sequences. Mixing experiments of known variants revealed that a certain proportion of 2 variants always resulted in the same proportion of both peaks in the sequencing gels.…”
Section: Microdissection and Fragment Length Analysismentioning
confidence: 99%
“…After controlling products on silver-stained polyacrylamide gels, samples were digested with HaeIII, creating a blunt end at np 333 immediately behind the polycytosine tract of interest. Using cloned and sequenced HVR2 fragments from an earlier study 21 and known HVR2 blood sequences, we could clearly determine the absolute length of the polycytosine tracts on a 373A sequencer (Applied Biosystems, Foster City, CA) by comparison with known sequences. Mixing experiments of known variants revealed that a certain proportion of 2 variants always resulted in the same proportion of both peaks in the sequencing gels.…”
Section: Microdissection and Fragment Length Analysismentioning
confidence: 99%
“…Chinnery et al (2002) suggested that random genetic drift is powerful enough to explain the fixation of rare mtDNA mutations during ageing, mtDNA disease, and cancer. In brain tumors, Kirches et al (1999) found high sequence variability in astrocytic brain cancers, as well as a loss of the heteroplasmy present in normal cells. In 2001, the same group extended the study of the HVS-II poly-C tract to 55 gliomas, detecting instability in five (9%) of them.…”
mentioning
confidence: 99%
“…According to the electrophoretic mobility of cloned and sequenced reference DNA in the gels, the peaks in the diagrams could be labelled with their absolute c-tract length. It is known12 and is supported by our own sequencing data10 that usually only the first half of the incomplete HVR2 c-tract exhibits length variability (fig 1). Therefore, the peak designations in fig 2 reflect only the number of cytosine residues within this region.…”
Section: Resultsmentioning
confidence: 60%
“…After controlling the products on silver stained PAGE gels, the samples were digested with Hae III, which creates a blunt end at np 333 immediately behind the c-tract of interest. Using cloned and sequenced HVR2 fragments from an earlier study10 and known HVR2 blood sequences, we could clearly determine the absolute c-tract length on a 373A sequencer (Applied Biosystems, Foster City, CA) by comparison with known sequences. Mixing experiments of known variants showed that a certain proportion of two variants always resulted in the same proportion of both peaks in the sequencing gels.…”
Section: Methodsmentioning
confidence: 99%